A hora e a vez do desenvolvimento regional brasileiro: Uma proposta de longo prazo - Liana Carleial; Bruno Cruz (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The actual momentum of the Brazilian Economy opens an opportunity to the country to discuss a strategy for regional development. Despite 60 years of regional development policies, regional disparities remain almost unchanged. Giving the boom of investment outside the main agglomeration in S\~ao Paulo and Rio de Janeiro, indentify complementarities and linkages among this new investment decision, which can lead the less developed region to diversify economy and increase local aggregation of value. Inspired by the work of Celso Furtado, for whom the heterogeneous nature of the economic structure and the lack of diversification in these economies are the source for external vulnerability, this paper presents some ideas and suggestion for a long run strategy of regional development policy. This new scenario of the Brazilian economy may allow the reversion of the situation.
Keywords: R58; 330; regional dynamics; regional development policies; economic development; Regionale Entwicklung; Regionalplanung; Brasilien